Hubungan Tehnik Menyusui Dengan Keteraturan Dalam Pemberian ASI Ekslusif Di Puskesmas Dambalo Kabupaten Gorontalo Utara Tahun 2024 - Darwis, Amelia; Amilah, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The majority of postpartum mothers experienced a decrease in pain after effleurage massage. Effleurage that is done gently and softly can reduce pain, create a sense of comfort and relax tension. Regularity in exclusive breastfeeding refers to a consistent breastfeeding Regularity in providing exclusive breastfeeding refers to a consistent breastfeeding schedule that is in accordance with the baby's needs, without being given other foods or drinks besides breast milk. This means that the baby is given breast milk regularly, both day and night, with a frequency and duration that are adjusted to his needs. This study aims to determine the relationship between breastfeeding techniques and the regularity of providing exclusive breastfeeding at the Dambalo Health Center, North Gorontalo Regency in 2024. The research design used Cross Sectional. The sample in the study, namely breastfeeding mothers at the Dambalo Health Center, was 47 people. Based on the results of the chi-square statistical test using the Statistical Program for Social Science (SPSS) application, the relationship between breastfeeding techniques and the regularity of providing exclusive breastfeeding is a p value of 0.001 <α = 0.05, which means that there is a relationship between breastfeeding techniques and the regularity of providing exclusive breastfeeding at the Dambalo Health Center, North Gorontalo Regency in 2024. It is recommended for the author as information on the importance of breastfeeding techniques with the regularity of providing exclusive breastfeeding. For Dambalo Health Center to conduct more frequent socialization and counseling on breastfeeding techniques and the regularity of exclusive breastfeeding. For the Government in general to design a breastfeeding training program that is more focused on improving breastfeeding techniques.